MANY FACTORS, MANY DIFFICULTIES, AND SOLVE THE PROBLEM OF SPEAKING ENGLISH: Bachelor of Science in Business Administration - Garry Alfonsius (Universal Journal, 2020)
Most of people can speak English but most of people cannot speak English that have many factors. Some people think English it’s not priority if you are not going outside from your country. But we know English language is an international language so we should learn it. Therefore, many people always say that English language is very hard to learn it but some people say English language really easy to learn it and they can practice with their teammate or with native speaker if they have the native speaker. The Indonesians who learnt English for their undergraduate program had been the population of this study. Although most of the students think that they have a good level of vocabulary or grammar, they also keep on feeling insecure while speaking. Most of the barriers were: being worried of making mistakes, feeling shy, and feeling frustrated while performing in English speaking.